Finance and Demand for Skill: Evidence from Uganda. Issue 12 (2nd December 2019) - Beck, Thorsten; Homanen, Mikael; Uras, Burak R.
Abstract: We explore the empirical interaction between firm growth, financing constraints, and job creation. Using a novel small-business survey from Uganda, we find that the extent to which small businesses expand skilled employment as their sales and profits increase is significantly related to access to external funding, while the hiring of casual and family workers is not. The results are robust to the inclusion of various firm level controls, region and sector fixed effects. We support our findings by providing empirical evidence on the relationship between planned hiring and firms' access to finance.